2016
DOI: 10.5578/khj.9559
|View full text |Cite
|
Sign up to set email alerts
|

Giant Right Atrium

Abstract: Severe enlargement of the atrium usually happens within the left atrium and is rarely seen in the right atrium. Giant right atrium is a rare condition that can be seen in tricuspid valve pathologies. Pulmonary hypertension, which could develop after tricuspid valve stenosis or insufficiency, may lead to giant right atrium in adults. A 45-year-old female patient was operated for tricuspid valve insufficiency related to a giant right atrium. Key Words: Pulmonary hypertension, right atrial dilatation Dev Sağ Atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
2
2
Order By: Relevance
“…However, the study group was too small to reach a definitive conclusion. The main difference between the cable groups in the Ozen et al [16] study and in our study was that our group consisted of moderately or severely obese patients. Furthermore, our surgical technique was of lower cost due to the utilization of two sternal cables on each patient compared with the use of three sternal cables in the Ozen et al [16] study.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…However, the study group was too small to reach a definitive conclusion. The main difference between the cable groups in the Ozen et al [16] study and in our study was that our group consisted of moderately or severely obese patients. Furthermore, our surgical technique was of lower cost due to the utilization of two sternal cables on each patient compared with the use of three sternal cables in the Ozen et al [16] study.…”
Section: Discussioncontrasting
confidence: 58%
“…The main difference between the cable groups in the Ozen et al [16] study and in our study was that our group consisted of moderately or severely obese patients. Furthermore, our surgical technique was of lower cost due to the utilization of two sternal cables on each patient compared with the use of three sternal cables in the Ozen et al [16] study. The sternal cable group of 24 patients in the study by Ozen et al revealed a satisfactory result with no postoperative sternal dehiscence.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations